Tinjauan Faktor Internal dan Eksternal dalam Psikoedukasional Problematika Akademik Siswa Sekolah Dasar - Aila Putri Wibowo; Habibah Nur Aini; Ridho Noviansyah; Tyas Agustin Anggraini; Sri Suwartini (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
Primary education is a crucial stage in establishing the foundation of students' knowledge, skills, and learning behavior. Nevertheless, various academic problems often emerge in elementary schools, such as difficulties in comprehending lessons, low learning motivation, and limited active participation. This research employs a literature review method with a qualitative approach to analyze the causes of academic issues in elementary schools. The findings reveal that internal factors involve motivation and learning interest, emotional intelligence and self-confidence, metacognitive skills and time management, as well as physical condition and health. Meanwhile, external factors include the family environment, school environment, peer influence, and social environment, as well as the utilization of technology and gadgets. A deep understanding of both types of factors is highly necessary for teachers and parents to develop flexible and responsive educational approaches to enhance the quality of learning.